Study of Argumentative Causal Relationship between Poverty and Population Growth in Sudan within the period (1980–2019) by using Vector Auto Regressive Model (VAR) - Osman, Hassan Ali; Hassan, Ezaldeen Abdel-Rahman; Musa, Fadul Alghali Elsued; Idris, Abdelgalal Osman (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to determine the form of the relationship and impact that the population growth in Sudan could have increased on poverty rate. To achieve this goal, a standard model for the relationship between the two previous variables was formulated and constructed during the period 1980-2019. Descriptive Analytical method was used in theoretical side of the study and tools of econometrics in analysis was used in practical side (VAR). The study assumed existence of direct relationship having a positive impact statistically between the population growth and poverty in Sudan. A standard model of non-significant impact have been obtained, whereby, the estimation results of Vector Auto Regressive showed that, there is no mutual significant impact between the poverty and population growth during term of the study. However, this result support results of mutual causality relationship both the variables. The study has recommended the necessity of controlling the population growth by legal ways in order to addressing the sources of defection which has been presented by the population growth.
Keywords: Poverty; Population Growth; Causal Debate